Community Based Tourism Dalam Pengembangan Pariwisata Bali - I Wayan Wiwin (UHN IGB Sugriwa Denpasar, 2018)
The tourism industry is currently growing, the potential of natural and culture resources continues to be developed as a tourist attraction. Tourism is not only owned by the government or entrepreneurs, tourism should also be owned by the local community. Therefore, tourism should be developed with a community-based concept. Community-based tourism is a form of tourism where local communities have control and are involved in development and management, and the proportion of benefits remains largely in the hands of local communities. Bali as one of the world's best tourist destinations has done just that. Many tourist attractionsin Bali have been managed with the concept of community-based tourism, such as Pandawa Beach and Kedonganan Beach in Badung regency, Tanah Lot in Tabanan regency, Monkey Forest Ubud and Ceking RiceTerraces in Gianyar Regency, and Penglipuran Village in Bangli Regency. CBT has been proven to improve the economy of local communities and be able to conserve natural and culture resources.